Maintaining Monarchy in Amidst Disruptive Era: Case Study of Kasultanan Ngayogyakarta, Indonesia - Jatmika, Sidik; Marlinda, Ajeng Puspa (WIMAYA, 2023)
Monarchy is an interesting political system to study because it is the earliest political system in world history and still exists today with various variations. This article focuses on the Yogyakarta Sultanate which was founded in 1755 as the only monarchy that still exists administratively in the political system of the Republic of Indonesia. This qualitative study finds that Yogyakarta's political system fulfil holistic, adaptive elements and combines old and new elements so that Yogyakarta gets asymmetric decentralization status from the republican central government of Indonesia. However, Yogyakarta has problems in the succession system because it does not yet have written and open rules like the British, Dutch, and Spanish monarchies. This study recommends the importance of a special study of the monarchy with all its survival capabilities in a modern democratic system.